Factory-Built Housing in Indonesia: Current Practice and Future Challenges - Andi asiz; Dicky R Munaf (Jurnal Teknik Sipil, 2005)
Abstract. Recent earthquake and tsunami in Aceh and North Sumatra has left Indonesia big responsibility in fulfilling housing need for people who lost their homes after this calamity. Use of mass-produced, factory-built systems for housing construction is technology that can be used as a solution to this problem. Factory-built housing can be defined as houses that are partly or all constructed in factory environment, then are transported and erected/assembled at permanent site. This paper is a summary of recent practices and potential development of factorybuilt housing in Indonesia by considering several Indonesian National Standard (SNI) which available. The aim of this paper is to explain the possibility of factory-built housing technology in Indonesia. The study synthesises information collected from review and analysis of trade and scientific literatures, a series of site visits to factorybuilt housing companies in industrialized countries; and discussions with academic institutions and building regulators in Indonesia. Definitions and types of factory-built systems are presented first followed by discussion of practical, regulatory, standards, and scientific issues applicable in Indonesia. Findings are identified as potential research needs in factory-built housing.Abstrak. Gempa dan tsunami yang baru terjadi di Aceh dan Sumatera Utara mengharuskan pemerintah Indonesia untuk menyediakan perumahan untuk masyarakat yang kehilangan rumah pasca musibah tersebut. Penggunaan sistem produksi massal konstruksi perumahan adalah suatu bentuk teknologi yang dapat dipakai untuk memecahkan masalah. Perumahan fabrikasi didefinisikan sebagai perumahan yang komponen-komponennya diproduksi di pabrik, kemudian dikirim dan dirangkai pada suatu tempat permanen. Makalah ini adalah ringkasan dari kondisi saat ini dan melihat potensi pengembangannya di Indonesia dengan mempertimbangkan SNI yang tersedia. Maksud dari paper ini adalah menjelaskan kebolehjadian penerapan teknologi perumahan fabrikasi di Indonesia. Studi yang dilakukan merupakan sintesa dari pengumpulan informasi dari kaji ulang dan analisis penerapan maupun kaji pustaka serta hasil kunjungan ke beberapa perusahaan terkait di negara maju, juga diskusi dengan institusi akademik dan regulator di Indonesia. Definisi dan jenis sistem perumahan fabrikasi ditampilkan yang disertai diskusi dari aspek praktis, regulasi, standard dan masalah saintifik di Indonesia. Dari pembahasan yang diberikan, ditemukan beberapa hal yang kiranya dapat menjadi potensi riset tentang topik yang dibahas.